Modellbasierte inverse Identifikation von Ultraschall-Transducern anhand der elektrischen Eingangsimpendanz - Bause, Fabian; Webersen, Manuel; Rautenberg, Jens; Henning, Bernd

Mixed methods analysis of enterprise social networks - Behrendt, Sebastian; Richter, Alexander; Trier, Matthias (Computer Networks)

Der richtige Ansprechpartner im dynamischen Interaktionsnetzwerk - Trier, Matthias; Müller, Matthias; Bobrik, Annette (HMD Praxis der Wirtschaftsinformatik)

MEDIA ENGINEERING WITH A CONTENT HUB SYSTEM. GENERIC CONTENT TRANSFORMATION FOR MOBILE MEDIA - Herzog, Michael; Trier, Matthias (International Journal of Computing)
A primary problem in multimedia content production is the plethora of formats and the resulting multiple point-to-point transformation processes in different content formatting specifications. However, these content transformation processes can be conceptually broken down into a limited set of abstract principles. This allows a unified approach that theoretically enables the transformation of any given input channel into any desired output. Based on this principle, the present article introduces the concept of Generic Content Transformation and the related project MOCCA, which develops the corresponding software implementation of generic content transformation for a variety of input and output channels. To balance technical similarities with specific properties of different media channels, we suggest a combination of an XML-based structure (MocML) and a high level authoring environment. Generic Content Transformation further allows for novel means of accessing assets via compound search algorithms. In the second part we summarize and discuss current results and experiences in three scenarios of media production, including mobile media.
Keywords: Multimedia Authoring; Mobile Content; Cross Media Production; Content Engineering; Media Retrieval

Business Intelligence 2.0 - Behrendt, Sebastian; Richter, Alexander; Schäfer, Sebastian; Trier, Matthias (Vernetzte Organisation)

Towards a Conceptualization of Online Community Health - Wagner, David; Richter, Alexander; Trier, Matthias; Wagner, Heinz-Theo (Proceedings of the 35th International Conference on Information Systems. ICIS 2014)
Along with the increasing popularity of social media and online communities in many business settings, the notion of online community health has become a common means by which community managers judge the condition or state of their communities. It has also been introduced to the literature, yet the concept remains underspecified and fragmented. In this paper, we work toward a construct conceptualization of online community health. Through a review of extant literature and dialogue with specialists in the field, we develop a multi-dimensional construct of online community health, consisting of seven elements. In writing this paper, we attempt to foster theory development around new organizational forms by advancing a new and important construct. The paper further provides guidance to the managers of social media and online communities by taking a systematic look at the well-being of their communities.
Keywords: Social media; Online communities; Online community success; Online community health; Construct conceptualization

Modeling intrinsic defects in LiNbO3 within the Slater-Janak transition state model - Li, Yanlu; Sanna, Simone; Schmidt, Wolf Gero (The Journal of Chemical Physics)

Modeling LiNbO3 Surfaces at Ambient Conditions - Hölscher, Rebecca; Schmidt, Wolf Gero; Sanna, Simone (The Journal of Physical Chemistry C)

The set of circular flow numbers of regular graphs - Schubert, Michael; Steffen, Eckhard (J. Graph Theory)

Petersen colorings and some families of snarks - Hägglund, Jonas; Steffen, Eckhard (Ars Mathematica Contemporanea)

PAC Rank Elicitation through Adaptive Sampling of Stochastic Pairwise Preferences - Busa-Fekete, Robert; Szörényi, B.; Hüllermeier, Eyke (Proceedings AAAI 2014, Quebec, Canada)

A Survey of Preference-Based Online Learning with Bandit Algorithms - Busa-Fekete, Robert; Hüllermeier, Eyke (Proceedings Int. Conf. on Algorithmic Learning Theory (ALT), Bled, Slovenia)

Mining Rank Data - Henzgen, Sascha; Hüllermeier, Eyke (Proceedings Discovery Science, Bled,Slovenia)

The Choquet kernel for monotone data - Fallah Tehrani, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings ESANN , Bruges, Belgium)

Learning Solution Similarity in Preference-Based CBR - Abdel-Aziz, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings Int. Conf. Case-Based Reasoning (ICCBR), Cork, Ireland)

Dyad Ranking Using A Bilinear Plackett-Luce Model - Schäfer, Dirk; Hüllermeier, Eyke (Proceedings Lernen-Wissensentdeckung-Adaptivität (LWA), Aachen, Germany)

Machine Learning and Knowledge Discovery in Databases-European Conf. ECML/PKDD, Nancy, France - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Proceedings, Parts I-III. Lecture Notes in Computer Science)

On Consumer Purchasing Behavior in Electronic Markets - Herrmann, Philipp

Preference Learning (Dagstuhl Seminar 14101) Dagstuhl Reports - Fürnkranz, J.; Hüllermeier, Eyke; Rudin, Cynthia; Slowinski, Roman; Sanner, Scott

Survival analysis on data streams: Analyzing temporal events in dynamically changing environments - Shaker, Ammar; Hüllermeier, Eyke (Applied Mathematics and Computer Science)

Ausgewählte Beiträge des GMA-Fachausschusses 5.14 - Hoffmann, F.; Hüllermeier, Eyke; Kroll, A. (Computational Intelligence Automatisierungstechnik)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Data Min. Knowledge Discovery)

Visualization of evolving fuzzy rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Rejoinder on "Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.- M.; Hüllermeier, Eyke (Neurocomputing)

Reliable classification: Learning classifiers that distinguish aleatoric and epistemic uncertainty - Senge, Robin; Bösner, S.; Dembczynski, K.; Haasenritter, J.; Hirsch, O.; Donner-Banzhoff, N.; Hüllermeier, Eyke (Information Sciences)

Protein Sub-Cellular Localization Prediction for Special compartments via Optimized Time Series Distances - Mernberger, M.; Moog, M.; Stork, S.; Zauner, S.; Maier, U.G.; Hüllermeier, Eyke (J. Bioinformatics and Computational Biology)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Machine Learning)

Preference-Based Reinforcement Learning: evolutionary direct policy search using a preference-based racing algorithm - Busa-Fekete, Robert; Szörényi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Dependent binary relevance models for multi-label classification - Montanés, E.; Senge, Robin; Barranquero, J.; Quevedo, J.R.; Del Coz, J.J.; Hüllermeier, Eyke (Pattern Recognition)

Open challenges for data stream mining research - Krempl, G.; Zliobaite, I.; Brzezinski, D.; Hüllermeier, Eyke; Last, M.; Lemaire, V.; Noack, T.; Shaker, Ammar; Sievi, S.; Spiliopoulou, M.; Stefanowski, J. (SIGKDD Explorations)

Extended Graph-Based Models for Enhanced Similarity Search in Cavbase - Krotzky, T.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Identification of Functionally Releated Enzymes by Learning to Rank Methods - Stock, M.; Fober, T.; Hüllermeier, Eyke; Glinca, S,; Klebe, G.; Pahikkala, T.; Airola, A.; De Baets, B.; Wageman, W. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Adsorption of PTCDA on Terraces and at Steps Sites of the KCl(100) Surface - Guo, Q.; Paulheim, A.; Sokolowski, M.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Oxygen adsorbates on the Si(111)4×1-In metallic atomic wire: Scanning tunneling microscopy and density-functional theory calculations - Oh, Deok Mahn; Wippermann, S.; Schmidt, Wolf Gero; Yeom, Han Woong (Physical Review B)

Geometrical and optical benchmarking of copper(II) guanidine-quinoline complexes: Insights from TD-DFT and many-body perturbation theory (part II) - Hoffmann, Alexander; Rohrmüller, Martin; Jesser, Anton; dos Santos Vieira, Ines; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

The atomic structure of ternary amorphous TixSi1−xO2hybrid oxides - Landmann, M; Köhler, T; Rauls, E; Frauenheim, T; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Formation of Hydroxyl Groups at Calcium-Silicate-Hydrate (C-S-H): Coexistence of Ca–OH and Si–OH on Wollastonite(001) - Sanna, Simone; Schmidt, Wolf Gero; Thissen, Peter (The Journal of Physical Chemistry C)

Rashba splitting and relativistic energy shifts in In/Si(111) nanowires - Gerstmann, Uwe; Vollmers, N. J.; Lücke, A.; Babilon, M.; Schmidt, Wolf Gero (Physical Review B)

IntrinsicLiNbO3point defects from hybrid density functional calculations - Li, Yanlu; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Temperature dependent LiNbO3(0001): Surface reconstruction and surface charge - Sanna, S.; Hölscher, R.; Schmidt, Wolf Gero (Applied Surface Science)

Unraveling theLiNbO3X-cut surface by atomic force microscopy and density functional theory - Sanna, S.; Schmidt, Wolf Gero; Rode, S.; Klassen, S.; Kühnle, A. (Physical Review B)

Power model design for ICT systems – A generic approach - Beister, Frederic; Dräxler, Martin; Aelken, Jörg; Karl, Holger (Computer Communications)

Design of an Electrical Interferometer at 120 GHz for Contactless Permittivity Characterization - Wessel, Jan; Schmalz, Klaus; Cahill, Brian; Scheytt, Christoph (Elektrotechnisches Kolloquium)

Architectural Low-Power Design Using Transaction-Based System Modeling and Simulation - Mischkalla, Fabian; Müller, Wolfgang (Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV))
Energy efficiency drives the development of more and more complex low-power designs. Based on dynamic power management techniques, multiple voltage islands as well as a huge amount of power states are specified that have to be tested carefully. In this context, low-power design should start at an early stage using state-of-the-art system-level modeling and simulation techniques. However, there is neither a programming language nor any modeling standard that reflects variable power together with its functional side effects in a well-suited abstract manner. To overcome this limitation, we present a modeling approach on top of SystemC TLM to capture low-power design characteristics at electronic system-level. We demonstrate the usability by means of an existing open-source low-power design. The experimental results show that appropriate TLM instrumentation cause only minimal simulation overhead, but offer sufficient details to identify common low-power design errors.

Switchable slow wave transmission line in 130 nm SiGe technology at 115 GHz for phase detection based biosensors - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik (Microwave Symposium (IMS), 2014 IEEE MTT-S International)
A 115 GHz slow wave transmission line intended for phase detection based integrated biosensors is presented. The structure was fabricated in a 130 nm SiGe process. It achieved the targeted overall phase shift of 1° at 115 GHz. Moreover, the phase can be adjusted by 16 switches using Heterojunction Bipolar (HBT) transistors leading to a phase resolution of 0.125°. The change in input and output matching over all configurations of the switches is not higher than 0.8 dB and the transmission S 21 varies with less than 0.7 dB. To the authors knowledge, it is the first switchable slow wave structure using microstrip transmission lines along with a bipolar switch circuitry. Moreover, the presented structure provides a very powerful solution for real-time digital read-outs in integrated biosensors, without need of additional signal processing steps.

A 7 GHz biosensor for permittivity change with enhanced sensitivity through phase compensation - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik; Cahill, Brian (European Microwave Conference (EuMC))
A calibration technique as well as measurement results for a 7 GHz Biosensor are presented. It is shown that the applied sensor structure can be calibrated by adjusting the phase of a sensing element's transmission S21. This is realized by slowing down the wave traveling a microstrip line serving as a reference in the differential sensor structure. The dielectric properties along with certain physical boundaries of an obstacle covering parts of the microstrip line evoke that effect. Measurements with an ethanol serious along with simulation results showed that sensitivity can be increased substantially with this calibration technique. A change of the real part of the sample's permittivity of 48 leads to a 18 MHz frequency shift.

Wireless 100 Gb/s: PHY layer Overview and Challenges in THz freqency band - Kraemer, Rolf; Wolf, Andreas; Scheytt, Christoph; Kallfass, Ingmar; KrishneGowda, Karthik (2014 IEEE 15th Annual IEEE Wireless and Microwave Technology Conference (WAMICON))
There is a continuous increase of bandwidth-demanding services such as ultra HDTV, 3D TV, etc. which will require data rates up to 100-400 Gb/s for short range wireless communication. This paper introduces a novel mixed-mode design where both analog and digital domain design is considered, which helps in the reduction of power consumption. Parallel Sequence Spread Spectrum (PSSS) is used for physical layer (PHY) baseband technology, which considerably alleviates both transmitter and receiver design.

Fast and Open Virtual Platforms for TriCore-based SoCs Using QEMU - Koppelmann, Bastian; Messidat, Bernd; Becker, Markus; Kuznik, Christoph; Müller, Wolfgang; Scheytt, Christoph (Design and Verification Conference (DVCON EUROPE))
In this paper, we present an efficient approach to virtual platform modeling for TriCore-based SoCs by combining fast and open software emulation with IEEE-1666 Standard SystemC simulation. For evaluation we consider Infineon's recently introduced AURIX processor family as a target platform, which utilizes multiple CPU cores operating in lockstep mode, memories, hierarchical buses, and a rich set of peripherals. For SoC prototyping, we integrate the fast and open instruction accurate QEMU software emulator with the TLMu library for SystemC co-verification. This article reports our most recent efforts of the implementation of the TriCore instruction set for QEMU. The experimental results demonstrate the functional correctness and performance of our TriCore implementation.